Preparation and in vitro Evaluation of Eudragit Microspheres Containing Theophylline - Chandra Rathi, Jagdish; Rathi, Vaishali; Kumar Jain, Hemant; Tamizharasi, S. (Asian Journal of Chemistry, 2010)
The aim of this study was to prepare and evaluate Eudragit (RS and RL) microspheres containing theophylline. Microspheres were prepared by solvent evaporation method using acetone/liquid paraffin system. The prepared microspheres were analyzed for particle size and shape, percentage yield, entrapment efficiency, stability study, in vitro release pattern and for release kinetics. The yield of preparation and the encapsulation efficiencies were high for all formulations. The maximum encapsulation efficiency was found to be 94.27 ± 1.36 % (w/w). No appreciable difference was observed in the extent of degradation of product during 60 d in the microspheres, which were stored at various temperatures. The in vitro release studies were carried out for a period of 7 h. Although theophylline release rate from Eudragit RS microspheres were very slow and incomplete, they were fast from Eudragit RL microspheres. When Eudragit RS was added to Eudragit RL microspheres formulation, release rate slowed down and achieved the release profile suitable for peroral administration. The release followed zero order kinetic.